Relative sea-level change, Kjove Land, Scoresby Sund, East Greenland: Implications for seasonality in Younger Dryas time - HALL B. L; DENTON G. H; KELLY M; LOWELL T.; BARONI, CARLO (Quaternary Science Reviews, 2008)
The age of the Milne Land Stade (MLS) moraines in the Scoresby Sund region of East Greenland is key for testing the hypothesis that strong seasonality marked abrupt cooling events, such as the Younger Dryas, registered in Greenland ice cores. The relevant chronology is based on 69 radiocarbon dates of shells from raised beaches and deltas related to marine inundation and isostatic rebound that accompanied glacier retreat from the moraines. Taken together, these dates form the basis for a relative sea-level curve that shows very high rates of emergence typical of recently deglaciated regions. Upward extrapolation of this curve suggests that the marine limit (134 m a.s.l.) dates to about 12,400 cal yr B.P. The shorelines that mark the marine limit lie within areas that were ice-covered when the glaciers were at the outer limit of the MLS advance; hence, the moraines that form the outer limit must antedate 12,400 cal yr B.P. and probably are from earliest Younger Dryas or Allerød time. At Holger Danskes Briller, an inner moraine grades to a massive ice-contact delta, now at 101 m a.s.l., which is dated to 11,000–11,300 cal yr B.P. The age of the outer MLS moraines, along with constraints on the maximum possible Younger Dryas ice extent and snowline lowering are consistent with the idea that East Greenland climate experienced strong seasonality during Younger Dryas time.